Challenging gender myths: Promoting inclusive wheat and maize research for development in Nepal - Farnworth, Cathy Rozel; Jafry, Tahseen; Lama, Kanchan; Chatterjee, Sushila; Badstue, Lone B. (International Maize and Wheat Improvement Center, 2018)
This technical note provides research evidence debunking four gender myths: 1) men are the main decision makers; 2) women don’t do much in wheat and maize; 3) women don’t innovate; and 4) women lack resources for innovation. Data is drawn from six GENNOVATE Nepal case studies in the Myagdi, Chitwan, Rupandehi, and Jajarkot Districts. The resource posits that understanding and working with women in wheat- or maize-related innovation processes will help to improve the design and relevance of innovations.